Man overboard - Jance, Judith A. (Jance, Judith A. Ali Reynolds mysteries., 2017)
Roger McGeary, a brilliant software engineer, has gifted himself with an upscale cruise in honor of his fortieth birthday. When he falls to his death from the balcony of his stateroom suite, the incident is quickly declared a suicide. Only his maiden aunt, a tough-as-nails woman who runs a race horse refuge refuses to take "case closed" for an answer and turns to Ali Reynolds at High Noon Enterprises to look into the situation.